Masseter muscle thickness and elasticity in periodontitis - Taşdemir, Zekeriya; Soydan, Damla; Alkan, Banu Arzu; Köy, Özge; Etöz, Meryem; ALKAN, BANU ARZU (My University, 2019)
This study aimed to compare the thickness and elasticity of the masseter muscle between patients with gingivitis and patients with periodontitis. A total of 124 patients (63 gingivitis, 61 chronic periodontitis) were recruited at the start of the study, but only 84 patients were declared as final participants. Patients were divided into two groups: (1) patients suffering from gingivitis and (2) those with generalized chronic periodontitis. Clinical (PI, plaque index; GI, gingival index; PD, probing depth; CAL, clinical attachment loss; and BOP, bleeding on probing scores) and ultrasonographic (thickness and elasticity of the masseter muscle) measurements of periodontitis were performed. There were no significant differences in gender, age, body mass index, education status, income level, or marital status between the two groups (P > 0.05). The mean age ± SD for the gingivitis and periodontitis groups was 39.5 ± 10.8 years and 44.8 ± 8.8 years, respectively. There were significant differences between the two groups in the number of PI, GI, PD, CAL, and BOP scores. There were significant differences between the two groups when thickness of masseter during contraction and at rest was taken into account. The gingivitis group had significantly thicker masseter during both contraction and rest. On the other hand, when the elasticity of the masseter was evaluated, there were no significant differences found between the two groups and two sides for each group. Masseter muscle thickness in the periodontitis group was found to be decreased compared with that in the gingivitis group. Furthermore, loss of periodontal tissues due to periodontitis reduces the masticatory ability
Keywords: Masseter muscle thickness; Periodontitis; Radiology; Public health